THE EFFECTIVENESS OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) AND GROUP INVESTIGATION (GI) TECHNIQUEsTO TEACH READING COMPREHENSION TO STUDENTS WITH HIGH AND LOW MOTIVATION - Chotimah, Nor; Rukmini, Dwi (Universitas Negeri Semarang, 2017)
This study aims to describe the significant difference between STAD and GI techniques to teach reading comprehension to students with high motivation, to describe the significant difference between STAD and GI techniques to teach reading comprehension to students with low motivation, to explain which one is more effective between STAD and GI techniques to teach reading comprehension to students with high and low motivation and to describe whether there is interaction among the teachniques, motivation, and teaching reading comprehension in this study.This study wass a quasi-experimental study. There were 26 students in the experimental and control group. They were divided into students with high and low motivation in each group. Test, questionnaire, and observation were used as the instruments of this study. The findings of this study are: there is significant difference between STAD and GI techniques to teach reading comprehension to students with high motivation, Student Team Achievement Division (STAD) technique is effective to teach reading comprehension to students with high and low motivation than Group Investigation (GI) technique, and there is no interaction among the techniques, motivation, and teaching reading comprehension. In conclusion, teaching reading comprehension of narrative text with Student Team Achievement Divivsion (STAD) technique is effective for students with high and low motivation. Thus, it is recommended that STAD technique be implemented in teaching reading comprehension.